Konsep Ideal Regulasi Identitas Digital Tunggal dalam Konvergensi Teknologi sebagai Instrumen Penguatan Perdagangan Digital Berbasis Ekonomi Virtual - Priyo Utomo, Aldi; Muhammad Ibrohim, Noor; Ramadhani, Nayla; Muhammad Zidni, Naufal; Stia Wahyuaristy, Delina (Forschungsforum Law Journal, 2025)
The development of the digital economy in Indonesia, which is driven by advances in information technology, requires adaptive and comprehensive regulations, one of which is the regulation of digital identity. A single digital identity is a vital instrument in ensuring security, validity, and trust in digital transactions. Unfortunately, legal arrangements in Indonesia are still sectoral and not fully integrated. Existing regulations such as the Electronic Information and Transaction Law, the Personal Data Protection Law, and Permendagri No. 72 of 2022 have not yet provided a complete and interoperable legal basis. This research uses a normative juridical method with a statutory approach, approach, comparative approach, and case approach. The discussion focuses on the urgency of establishing a single digital identity regulation, compared to the Electronic Identification, Authentication and Trust Services (eIDAS) in the European Union which has implemented a comprehensive cross-country digital identity system, and formulating the ideal regulatory concept applied in Indonesia. The results of the study show the need for the establishment of a separate regulation on a single digital identity that contains aspects of definition, technical infrastructure, legal guarantees, digital trust services, and protection of user rights. The ideal concept of regulation must also be based on philosophical (values of Pancasila and the 1945 Constitution), sociological (demands for public needs for digital identity security), and juridical (to fill the legal vacuum) foundations. Therefore, a single digital identity regulation is expected to become a strong legal foundation to support digital trade based on the virtual economy in a fair and sustainable manner.